Respiratory Fungal Co-Infections in Covid-19 Patients - Guragain, Ankita; Bhusal, Yuvaraj; Rayamajhi, Sulav; Bhattarai, Sanjeet; Shrestha, Sanjeet Krishna (Nepalese Respiratory Journal, 2024)
Background: Coronavirus disease 2019 (COVID-19), caused by a novel coronavirus (SARS-CoV-2), has been known to cause mild respiratory illness to severe pneumonia. During its pandemic, an increase in viral, bacterial, and fungal coinfections was observed. With Candida, Aspergillus, and Mucor species being the primary fungal pathogens causing secondary pulmonary infections. Risk factors such as prolonged immunosuppressive drug use and comorbidities such as diabetes mellitus and solid organ transplantation increase susceptibility to these coinfections.Objective: The study aimed to determine the incidence of pulmonary candidiasis, invasive aspergillosis, and pulmonary mucormycosis in COVID-19 patients and evaluate various risk factors.Methods: Lower respiratory samples from COVID-19 patients with suspected fungal coinfections were analyzed microbiologically. Macroscopic features such as the morphology of colonies and microscopic characters such as the presence or absence of septations in hyphae, the arrangement of hyphae, the arrangement of conidiophores and conidia, and the presence or absence of rhizoids on lactophenol cotton blue (LPCB) mounts were used for the identification of molds. Morphology of colony, Gram stain, and germ tube test were used for identification of Candida spp.Results: Of 1789 suspected cases, 216 (12.1%) showed positive fungal culture, predominantly in males (67.9%). Candida spp. accounted for 62.9% of cases, followed by Aspergillus spp. (22.2%) and Mucor spp. (7.4%), with 7% showing mixed Aspergillus and Candida infections. Non-albicans Candida spp. were the most common Candida spp., followed by Aspergillus flavus, fumigatus, and nidulans, and Rhizopus among Mucorales. All of the COVID-19 patients were under steroid therapy, and 89.8% of patients had immunocompromising conditions, primarily diabetes mellitus (76.2%), followed by hypertension (14%), both diabetes and hypertension (9.3%), and organ transplantation (0.5%).Conclusion: COVID-19 is associated with a high number of respiratory fungal coinfections, driven by prolonged hospitalization, steroid use, and comorbidities. Careful measures should be adopted by healthcare professionals to minimize the risk of respiratory fungal coinfections and associated fatality.